Analysis of the utilization and cost of antibiotics at an intensive care unit in Surabaya - Eko Setiawan; Hidayat Felix; Adji Prayitno Setiadi (Universitas Ahmad Dahlan, 2017)
The appropriateness of antibiotic utilization including the compatibility when it was mixed with other pharmaceutical products are important factors determining the effectiveness and cost of antibiotics treatment among patients admitted to the intensive care unit (ICU). The aim of this research was to figure out the antibiotics utilization, appropriateness, cost, and compatibility profile given to the inpatients of the intensive care unit in one hospital in Surabaya during November-December 2015. This research was prospective observational study using medical records as source of information. All patients’ data receiving antibiotics that met the inclusion and exclusion criteria was collected and analyzed descriptively. There were 42 patients participated in this research. Analysis of antibiotic utilization profile revealed 46 usage (65.71%) of single antibiotics and 24 usage (34.29%) of combination antibiotics. The most frequently used of antibiotic in single usage was ceftriaxone (43.48%) while in combination were ceftazidime and levofloxacin (12.50%). There were 30 antibiotics treatment changes that 43.34% was classified as escalation process and there was no (0%) any switching from intravenous to oral therapy. Only 4 out of 15 patients with infection related diagnosis (26.67%) got appropriate antibiotic treatment. Moreover, result from compatibility analysis found that 13.96% admixtures between antibiotics and other intravenous pharmaceutical products did not have clear compatibility status. The average of antibiotic cost per-patient was Rp. 459.492 (min-max: Rp 15.852,- to Rp 8.314.914,-).